Room [videorecording (DVD)] - Larson, Brie, 1989-; Tremblay, Jacob; Bridgers, Sean; Park, Megan, 1986-; Macy, William H., 1950-; Donoghue, Emma, 1969- (Lionsgate, 2016)
After five-year old Jack and his Mom escape from the enclosed environment that Jack has known his entire life, the boy makes a miraculous discovery: the outside world.